Environmental Health Risk Assessment of Phthalic Acid Esters in Drinking Water Source Catchments of South China - He, Tao; Fang, Huaiyang; Guan, Wei; Luan, Zhenyu; Wei, Dongyang; Fan, Jiajun (Journal of Environmental Accounting and Management, 2026)
In recent years, phthalic acid esters (PAEs) have been widely detected in drinking water sources in China, threatening environmental health and has therefore become an urgent demand for environmental health risk assessment. Through the analysis of water quality testing at a South China backup water source, we detected PAEs. The results show that the PAE class pollutants, phthalic acid n-butyl acetate (DBP), phthalate (2-) ethyl hexyl ester (DOP) and diethyl phthalate (DEP), are detected at all sampling points, with DOP concentrations higher than that of DBP and DEP. The quantified concentration of the three PAE pollutants in the drinking water catchment area is higher than that of other drinking water sources in other towns in the basin, and the concentration is also above the median-level in similar areas at home and abroad. DOP is the primary PAE pollutant controlled by domestic demand in the catchment area. In this paper, we made an environmental health risk assessment for the PAE class of organic pollutants in the backup water source using the United States Environmental Protection Agency (EPA) method. The results show that the carcinogenic and noncarcinogenic risk values associated with PAEs for the water source are less than the provisions of USEPA but that the PAE concentrations are elevated relative to domestic and similar foreign water sources. Given the potential health risks of PAEs, water environment risk management should guard against the possible sources of PAEs.